Crystal structure of a repair enzyme of oxidatively damaged DNA, MutM (Fpg), from an extreme thermophile, Thermus thermophilus HB8 - Sugahara, Mitsuaki (Oxford University Press, 2000)
The MutM [formamidopyrimidine DNA glycosylase (Fpg)] protein is a trifunctional DNA base excision repair enzyme that removes a wide range of oxidatively damaged bases (N-glycosylase activity) and cleaves both the 3′- and 5′-phosphodiester bonds of the resulting apurinic/apyrimidinic site (AP lyase activity). The crystal structure of MutM from an extreme thermophile, Thermus thermophilus HB8, was determined at 1.9 Å resolution with multiwavelength anomalous diffraction phasing using the intrinsic Zn(2+) ion of the zinc finger. MutM is composed of two distinct and novel domains connected by a flexible hinge. There is a large, electrostatically positive cleft lined by highly conserved residues between the domains. On the basis of the three-dimensional structure and taking account of previous biochemical experiments, we propose a DNA-binding mode and reaction mechanism for MutM. The locations of the putative catalytic residues and the two DNA-binding motifs (the zinc finger and the helix–two-turns–helix motifs) suggest that the oxidized base is flipped out from double-stranded DNA in the binding mode and excised by a catalytic mechanism similar to that of bifunctional base excision repair enzymes.